Epidemiology, aetiology and treatment of skin and soft tissue infections: final report of a prospective multicentre national registry. (17th November 2022) - Esposito, Silvano; Pagliano, Pasquale; De Simone, Giuseppe; Pan, Angelo; Brambilla, Paola; Gattuso, Gianni; Mastroianni, Claudio; Kertusha, Blertha; Contini, Carlo; Massoli, Lorenzo; Francisci, Daniela; Priante, Giulia; et al.
Abstract: Skin and soft tissue infections (SSTIs) represent a heterogenous group of pathological conditions involving the skin or the underlying subcutaneous tissues, fascia and muscle, characterised by a considerable variety of clinical presentations, severity and possible aetiological pathogens. Although previous analyses on restricted types of SSTIs and population have already been published, we conducted a large nationwide surveillance program on behalf of the Italian Society of Infectious and Tropical Diseases to assess the clinical and microbiological characteristics of the whole SSTI spectrum, from mild to severe life-threatening infections, in both inpatients and outpatients and their management. Twenty-nine Infectious Diseases (ID) Centres throughout Italy collected prospectively data concerning both the clinical and microbiological diagnosis of patients affected by SSTIs via an electronic case report form. We included in our database all cases managed by ID specialists participating to the study, independently from their severity or the setting of consultation. Here, we integrated previous preliminary results analysing and reporting data referring to a 3-year period (October 2016–October 2019). During this period, the study population included 478 adult patients with diagnosis of SSTI. The type of infection diagnosed, the aetiological agent involved and some notes on antimicrobial susceptibilities were collected and reported herein. We also analysed the most common co-morbidities, the type and duration of therapy executed, before and after ID intervention and the length of stay. The results of our study provide information to better understand the national epidemiologic data and the current clinical management of SSTIs in Italy.